Evaluation of Piezoelectric-based Composite for Actuator Application via FEM with Thermal Analogy - Kevin, Alexander; Akbar, Mahesa; Gunawan, Leonardo; Aulia, Darryl Khalid; Agung, Rizqy; Rawikara, Seno Sahisnu; Sasongko, Rianto Adhy; Widagdo, Djarot (European Journal of Computational Mechanics, 2023)
In the present work, a new study on the piezoelectric-based structure by means of Finite Element Method (FEM) is conducted. Currently, the piezoelectric model in the FEM-based commercial software is only applicable via 2D plane stress and 3D solid elements. However, piezoelectric structures are usually manufactured as thin-walled structures, i.e., plates and disks. Therefore, it is more convenient to model a piezoelectric-based structure with 2D shell elements. In this study, FEM with a thermal analogy approach is implemented. Thermal coupling characteristics are utilised as the equivalent of electromechanical properties. Thermal analysis is much more established in FEM-based software; thus, applications with various types of elements are enabled. Therefore, the evaluation of piezoelectric structure via shell element with a thermal analogy approach could be performed. Static and dynamic analyses are conducted with experimental and numerical validations. As depicted in some details in this paper, the shell model with thermal analogy shows an excellent agreement with the 3D solid piezoelectric elements with insignificant variances, less than 0.3%.